Effects of upstream square blockage on lift behaviour of a rotating cylinder - Cheong, Xiang Hou (2016)
The usage of Unmanned Aerial Vehicle (UAV) is getting more and more significant in both the defense and commercial industry. As these UAVs normally carry a high payload and require a long runaway, it is important to develop a new method to increase the lift coefficient during takeoff and landing. The objective of the study is to study the lift generated by rotating cylinder at different spin rate at typical takeoff speed and also the effect upstream square blockage towards the lift generated by the rotating cylinder. Both wind tunnel experimental testing and numerical simulation was carried out to investigate the effect of different size of upstream blockage towards the performance of the rotating cylinder. The simulation adopted a fully turbulent flow, having Reynolds number varying from 5000 to 8000 and angular velocity of rotating cylinder varying from 0 to 3000 RPM. Validation of RANS code ANSYS Fluent was done with experimental results. The simulations results suggest that the blockage with the height of 32mm and 40mm, width of 8mm with a distance of 48mm from the center of the rotating cylinder will be the best configuration with near to tenth fold improvement in lift generation